International Timetabling Competition 2019: a systematic literature review - Abdipoor, Sina; Yaakob, Razali; Goh, Say Leng; Abdullah, Salwani; Kasmiran, Khairul Azhar; Hamdan, Hazlina (IEEE, 2023)
The University Course Timetabling Problem is an active and complex field with broad implications at most educational institutions. The current gap between literature and real-world applications is among the foremost challenges in this domain. This gap can be attributed to the solvers’ lack of generality and/or inconsistency in problem definition. In an attempt to tackle this issue, the Student Sectioning Problem has been incorporated into the latest International Timetabling Competition benchmark dataset. This paper reviews, categorizes, and summarizes the approaches addressing the University Course Timetabling with Student Sectioning Problem. Furthermore, the strengths and limitations of these methods are analyzed. Challenges, gaps, and possible future work are also presented.